Incidence and survival of lymphoid neoplasms in Spain, 2002-2013: A population-based study from the Spanish Network of Cancer Registries (REDECAN) - Pla, Clàudia; Solans, Marta; Ameijide, Alberto; Sanvisens, Arantza; Carulla, Marià; Rojas, María Dolores; Alemán, María Araceli; Sáez-Lloret, Isabel; Díaz-del-Campo, Cristina; Marcos-Navarro, Ana Isabel; Sainz-de-Aja, Leire; Aizpurua-Atxega, Amaia; et al. (Frontiers in Oncology, 2022)
The aim of this study was to describe incidence, incidence trends and survival patterns of lymphoid neoplasms (LNs) and its subtypes in Spain in the period 2002-2013 using data from the Spanish Network of Cancer Registries (REDECAN). Data were extracted from 13 Spanish population-based cancer registries. LNs incident cases were codified using the International Classification of Diseases for Oncology, third edition (ICD-O-3) and grouped according to the WHO 2008 classification. Age-standardized incidence rates to the 2013 European standard population (ASIRe) were obtained. Poisson regression models were used to analyze trends in incidence. Observed survival (OS) was estimated by the Kaplan-Meier method and net survival (NS) by the Pohar-Perme method. Sex- and age-specific estimates of 5-year NS were calculated, as well as its changes according to two periods of diagnosis (2002-2007 and 2008-2013). LNs accounted for 69% (n=39,156) of all hematological malignancies (n=56,751) diagnosed during the period of study. Median age at diagnosis was 67 years (interquartile range (IQR) = 52-77). The overall ASIRe was 34.23 (95% confidence interval (CI): 33.89, 34.57) and showed a marked male predominance in almost all subtypes (global sex ratio = 1.45). During the study period, incidence trends of LNs remained stable (APC: 0.3; 95% CI: -0.1, 0.6), nevertheless some subtypes showed statistically significant variations, such as LNs NOS category (APC: -5.6; 95% CI: -6.8, -4.3). Around 17,926 new cases of LNs will be diagnosed in 2023 in Spain. Survival rates differed considerably across age-groups, while they were similar between men and women. Five- year NS was 62.81% (95% CI: 62.1, 63.52) for all LNs, and varied widely across LNs subtypes, ranging from 39.21% to 90.25%. NS for all LNs improved from the first period of diagnosis to the second one, being 61.57% (95% CI: 60.56, 62.61) in 2002-2007 and 64.17% (95% CI: 63.29, 65.07) in 2008-2013. This study presents the first complete and extensive population-based analysis of LNs incidence and survival in Spain. These population-based data provide relevant information to better understand the epidemiology of LNs in Southern Europe and it features some useful points for public health authorities and clinicians.